A proposed modulatory role of the endocannabinoid system on adipose tissue metabolism and appetite in periparturient dairy cows - Madison N. Myers; Maya Zachut; Joseph Tam; G. Andres Contreras (Journal of Animal Science and Biotechnology, 2021)
Abstract To sustain the nutrient demands of rapid fetal growth, parturition, and milk synthesis, periparturient dairy cows mobilize adipose tissue fatty acid stores through lipolysis. This process induces an inflammatory response within AT that is resolved as lactation progresses; however, excessive and protracted lipolysis compounds the risk for metabolic and inflammatory diseases. The suppression of lipolytic action and inflammation, along with amplification of adipogenesis and lipogenesis, serve as prospective therapeutic targets for improving the health of periparturient dairy cows. Generally, the activation of cannabinoid receptors by endocannabinoids enhances adipogenesis and lipogenesis, suppresses lipolysis, and increases appetite in mammals. These biological effects of activating the endocannabinoid system open the possibility of harnessing the endocannabinoid system through nutritional intervention in dairy herds as a potential tool to improve dairy cows’ health, although much is still to be revealed in this context. This review summarizes the current knowledge surrounding the components of the endocannabinoid system, elaborates on the metabolic effects of its activation, and explores the potential to modulate its activity in periparturient dairy cows.